Functional outcomes of artificial urinary sphincter implantation with distal bulbar double cuff in men with and without a history of external beam radiotherapy: an analysis of a prospective database. (26th August 2019) - Maurer, Valentin; Marks, Phillip; Dahlem, Roland; Rosenbaum, Clemens M.; Meyer, Christian P.; Riechardt, Silke; Fisch, Margit; Ludwig, Tim
Abstract : Objectives: To analyse functional outcomes and complication rates of artificial urinary sphincter (AUS) implantation with a distal bulbar double cuff (DC) for the treatment of stress urinary incontinence (SUI) in men with and without a history of external beam radiotherapy (RT). Patients and Methods: Data of all patients undergoing AUS implantation with a distal bulbar DC (DC‐AUS) were collected prospectively from 2009 to 2015. Indications for DC implantation were based on urethral risk factors in terms of RT and previous proximal bulbar urethral interventions including, endoscopic or open surgery for urethral stricture or SUI. Implantation was carried out to a standardised protocol. Activation of the AUS was performed 6 weeks after implantation. Further follow‐up (FU) included pad test, uroflowmetry, post‐void residual urine measurements, radiography, and a standardised questionnaire. Continence and complication rates were compared between patients with a history of RT and non‐RT patients. Explantation‐free survival was estimated using Kaplan–Meier curves and the log‐rank test. Firth's penalized Cox‐regression analyses were performed to analyse proportional hazard ratios for explantation. Results: In all, 150 men (median age 70 years, interquartile range [IQR] 66–74) after DC‐AUS implantation were available for analysis. Overall, 73 men (48.7%) had a history of RT. The median (IQR) FU was 24 (7.25–36) months. Baseline clinical characteristics only differed regarding previous open SUI surgery ( P  = 0.016). Social and objective continence was achieved in 94.8% and 84.3% of all patients treated by implantation of a DC‐AUS, respectively. Between the RT and non‐RT patients there were no statistically significant differences in continence rates [social continence: 100% vs 90.2% ( P  = 0.194); objective continence: 87% vs 82% ( P  = 0.877)]. For complications rates there were no significant differences between RT and non‐RT patients after DC‐AUS implantation [infection ( P  = 0.09), erosion ( P  = 0.31), mechanical failures ( P  = 0.14)]. According to Kaplan–Meier analysis explantation rates in patients with a history of RT (26.0%) vs non‐RT patients (20.8%), estimated explantation‐free survival, and AUS durability, did not differ significantly (log‐rank P  = 0.219). Conclusion: Our data from a large institutional series indicate DC‐AUS implantation to be an effective and safe treatment strategy in men with SUI and a history of RT.